Hukum Jual Beli Tinja sebagai Pupuk Menurut Pandangan Empat Imam Mazhab : Law on the Sale and Buying of Feces as Fertilizer According to the Views of the Four Imam Schools - Ariesman M.; Patuti, Asnawati; Yuniar Kamboja (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to examine and understand the legal status of trading feces processed into fertilizer from the perspective of the four major Islamic schools of thought (mazhab). The primary issues addressed in this research are: first, the process of converting feces into usable fertilizer; second, the legal perspectives of the four mazhab on the trade of feces as fertilizer. This research adopts a library-based approach (library research), focusing on textual and manuscript studies using normative, historical, and comparative methods. The findings reveal two key points. First, the process of converting feces into usable fertilizer involves several stages: the feces are initially dried and then mixed with other materials such as rice husks, sawdust, manure, and kitchen waste, including spinach, tomatoes, or spoiled rice. Subsequently, the mixture is treated with fermentation liquid to facilitate decomposition. Second, the four mazhab offer differing views regarding the legality of trading feces as fertilizer. The Shafi’i school prohibits the trade of feces as fertilizer, as feces are considered impure (najis) and thus forbidden for trade. In contrast, the Hanbali and Maliki schools permit the trade of such fertilizer, provided the feces come from areas where the local population consumes lawful food. The Hanafi school, meanwhile, allows the trade of feces-based fertilizer on the grounds that it serves a beneficial purpose.